Development of Traditional Market Garbage Bin - Ma'ruf, Farid; Anrian, Wahyu; Arum, Isana (Jurnal PASTI (Penelitian dan Aplikasi Sistem dan Teknik Industri), 2024)
A garbage bin is a tool for handling waste in the Demangan and Sentul markets. Garbage leachate is terrible for the environment and humans and is a location for Aedes aegypti mosquitoes to breed due to ammonia compounds in leachate. This research aims to redesign the garbage bin so that it is optimal for controlling and managing waste and minimizing its impact. The garbage bin is designed using the Quality Function Deployment method. The garbage bin design has nine attributes from the customer's voice and sixteen technical response attributes. The technical response attribute becomes the part deployment input, resulting in twenty one part specification attributes. The priority attribute divides the shelter into two parts: the organic and non-organic waste has CW=662.16. The developed garbage bin design advantages are storage space according to type, wastewater storage, and minimizing waste's destructive impact.